The Chicago Municipal Code of 1922, Article II, Regulations, Sec. 2870 (1922) - (:unkn) unknown (General Publisher, 1922)
Prohibited carry of firearms, throwing stones, or other missiles in any of the parks, public playgroudnds, or bathing beaches in the city. Prohiited cutting, breaking, or injuring trees, shrubs, plants, turf, fences, bridges, or other construction or property contained therein.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES